Efecto de nanopartículas de cobre sobre la capacidad de regeneración de Dugesia tigrina - CORNEJO ROQUE, Brian Enrique (2019)
The present investigation determined the effect of four concentrations of copper nanoparticles (0%, 25%, 50% and 100%) on the regeneration capacity of Dugesia tigrina, for which, cuts of various types were made, including; transversal, double transversal and longitudinal, of which different fragments of the upper and lower region, cephalic, middle and caudal fragments, and left and right fragments were obtained. These fragments were exposed to the treatments constituted by the different concentrations of copper nanoparticles, subsequently, the measurements of the blastema formation times as well as of the entire individual were made. When the readings were made in the optical microscope, it was observed that the T4 treatment (100% NPsCu) produced a greater reduction in the time of blastema formation, for each of the types of fragment of Dugesia tigrina, being the upper fragment (Block I) who developed blastema in less time (69.70 hours) .In addition, the T4 treatment (100% NPsCu) produced the greatest reduction in the time of complete individual formation, for each of the fragment types of Dugesia tigrina, being the superior fragment (Block I) who formed a complete individual in the shortest time (215.2 hours). The analysis of variance was performed, the presence of statistically significant differences between treatments was determined.